The long- and short-run relationship between the shadow economy and trade openness in Uganda - Stephen Esaku (Cogent Economics & Finance, 2021)
This paper examines the relationship between the shadow economy and trade openness in Uganda, using autoregressive distributed lag bounds testing approach. We find that the shadow economy and trade openness have a long- and short-run relationship. These results hold even when alternative econometric methods are used. The empirical evidence indicates that more exposure to foreign trade significantly reduces the size of the shadow economy. This could imply that as countries become more integrated into the world economy, firms and individual entrepreneurs are induced to engage in the formal sector so as to reap the benefits of international markets. This paper shows that trade openness is an important determinant of the shadow economy in both the short- and long-run. At the policy level, any policy framework that strengthens integration into the global economy will be an effective tool that can reduce shadow activities in both the short- and long-run. The practical implication of these results is that countries that have fully reformed their economies to allow for free trade and investment inflows experience a decline in shadow activities implying that, in more open economies, more trade reduces informality.
Keywords: F10; F14; F61; O17; P10; 330; Globalization; informal sector; shadow economy; trade; trade openness